A CONCEPTUAL FRAMEWORK: MANAGERIAL DECISION MAKING STYLES AND ORGANIZATIONAL EFFECTIVENESS AMONG DEANS OF MALAYSIAN PUBLIC UNIVERSITIES - Jamian, Leele Susana; Sidhu, Gurnam Kaur; Aperapar, Parmjit Singh (UPI Press, 2011)
Scholars in the area of management agree that decision making is both central andfundamental to any organization. This is because the quality of decisions made wouldinfluence the effectiveness of the managers and consequently, affect the success of thewhole organization. Indeed, this also happens in the educational management setting.Drawing from an ongoing doctoral research which looked at the relationship betweenmanagerial decision making styles and organizational effectiveness among deans ofMalaysian public universities, this article discusses the formulation of a conceptualframework. The framework put forward in this paper is based on both literature anda study investigating the relationship between managerial decision making styles andorganizational effectiveness among deans of Malaysian public universities. Second,the paper also attempts to discuss the possible research issues that could justify thedevelopment of the conceptual framework of the topic. Literature reveals that there arepotential links pointing to the relationships between the variables. However, as to datethere is little empirical scholarly research conducted in the educational management andleadership setting concerning the variables discussed in this study.Keywords: Decision making styles, decision making skills, organizational effectiveness,deans.